Delayed Persistent Intermittent Edema (DPE) after hyaluronic acid use - challenges and clinical approaches: A case report (Research, Society and Development, 2024)
Hyaluronic Acid (HA) is widely used in the world of facial harmonization, its use requires a high knowledge of the anatomy and the technique to be used when applying it, although it is a safe material, it can generate complications. In this context, this article's objective is to present a clinical case report of a 29-year-old patient who developed Delayed Persistent Intermittent Edema (DPE) and presented this condition one year after undergoing lip filling with HA, triggered during an episode of flu. The proposed treatment was sessions of dexamethasone, a synthetic glucocorticoid with powerful anti-inflammatory action, and photo biomodulation, a technique that uses low-intensity light to stimulate tissue regeneration. The treatment proved effective, with complete resolution in seven days and no recurrence after one year of follow-up. The article highlights the importance of accurate diagnosis and adequate management of late HA complications, proposing effective therapeutic strategies to ensure greater safety and effectiveness in aesthetic procedures.